Study on Thermal Conductivities of CaCl2/ENG Composite Adsorbents - Gao Jiao; He Yan; Lin Yan; Yang Xiao (Zhileng xuebao)
In order to study on the heat transfer performance of Cacl2/ENG, the solidified composite adsorbents with 4 different molding pressure and 3 different kinds of ratio between Cacl2 and expanded natural graphite have been developed. Meanwhile thermal conductivity of samples is tested with Nai Chi LFA447 conductivity Meter. The experiment results show that: in a certain range, the thermal conductivity increases with the increase of molding pressure under the same ratio and the thermal conductivity decreases with the ratio increases under the same molding pressure. In all the test samples, the thermal conductivity of consolidated composite adsorbents is reached its highest 2.7 W/ (m?K) when molding pressure is 1.7KN and the ratio of Cacl2/ENG is 2:1.